IMPLEMENTASI KURIKULUM 2013 SMK NEGERI KOMPETENSI KEAHLIAN TEKNIK GAMBAR BANGUNAN DI DKI JAKARTA - Hadi Sumantri (Jurnal Pensil : Pendidikan Teknik Sipil, 2016)
This research was aimed in order to know the implementation of 2013 Curriculum at Contruction Technical Drawing Competence on the aspects of: (1) Teachers’s standard of assessment, (2) The standard of teacher and education staff in this case the competence of teacher and headmaster, (3) The standard of facilities. This research is comprise to desriptive and quantitative research. The populationo this research was the entire of State Vocational High Schools in DKI Jakarta which have implemented 2013 Curriculum. There were 3 schools as research sample which was gotten by simple random sampling method. The respondents consisted of 3 vice principals of Curriculum, 3 head of contructrion technical drawing competence, and 10 representative students of each teacher in the school. The data collection of this research was gotten by questionnaire, observation, and documentation. The result of this research showed that the aspects of : (1) the teacher’s standard of assessment at the schools whic implemented 2013 Curriculum reached the average 83 % in very good criteria, (2) the standard of teachers and education staff reached the average 83 % in very good criteria for teachers competence, and the average 73 % in good criteria for headmaster competence, (3) the standard of facilities that support the implementation of 2013 Curriculum reached the average 94 % in very good criteria